Comparison of the Effectiveness of Attachment-Based Play Therapy and Cognitive-Behavioral Therapy on Emotional Regulation and Quality of Life in Children with Separation Anxiety Disorder - Shamsabadi, Fatemeh; Mirzaian, Bahram; Abbasi, Ghodratollah (KMAN Counseling & Psychology Nexus, 2024)
The purpose of the present study was to compare the effectiveness of attachment-based play therapy and cognitive-behavioral therapy on emotional regulation and quality of life in children with separation anxiety disorder. The research method was a quasi-experimental design with a pre-test-post-test and control group. The statistical population of this study consisted of all male and female first-grade students who visited the psychological disorder treatment center in the city of Gorgan during the 2023-2024 academic year. The sample size for the experimental and control groups was calculated using G-Power software, considering inclusion criteria, a power of 0.85, an effect size of 0.40, an alpha level of 0.05, and 3 degrees of freedom for three groups, totaling 45 samples. These were randomly assigned to two experimental groups of 15 participants each and one control group of 15 participants. To collect data, the Emotion Regulation Questionnaire by Gross and John (2003) and the Quality of Life Questionnaire by Varni et al. (2003) were used. A summary of the attachment-based play therapy sessions was derived from Booth and Jernberg (2009) and conducted in 10 sessions of 45 minutes each. The summary of the cognitive-behavioral therapy sessions was based on Kendall (1994) and conducted in 16 sessions of 45 minutes each. No intervention was conducted for the control group. Data analysis was performed using repeated measures analysis of variance with SPSS 18 software. The results showed that both attachment-based play therapy and cognitive-behavioral therapy had an impact on emotional regulation and quality of life in children with separation anxiety disorder (p < 0.01). Attachment-based play therapy was more effective than cognitive-behavioral therapy in reducing separation anxiety and improving the parent-child relationship, while cognitive-behavioral therapy was more effective than attachment-based play therapy in improving emotional regulation and quality of life. The findings of this study may provide practical implications for therapists and counselors.